GRIT PADA SISWA SEKOLAH MENENGAH DAN IMPLIKASINYA PADA LAYANAN BIMBINGAN DAN KONSELING - Agis Kurnia; Anandha Putri Rahimsyah; Cucu Arumsari (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
Grit is one of the non-cognitive factors that plays an important role in supporting students in achieving long-term goals. However, based on observations and interviews conducted with guidance and counseling teachers at SMPN 1 Karangnunggal, several students still demonstrate low levels of perseverance and consistency in learning. This study aims to identify students' grit levels and develop a reality counseling program to enhance students' grit at SMPN 1 Karangnunggal. This study employed a quantitative approach using a descriptive method. The population consisted of seventh and eighth-grade students at SMPN 1 Karangnunggal. Data were collected using a grit instrument developed based on the aspects of perseverance, persistence, and adversity. The data were analyzed using descriptive statistics. The findings indicate that students' grit levels are generally in the moderate category. These findings suggest that students still require guidance and counseling services to improve their perseverance and consistency in dealing with academic challenges. Based on the findings, a reality counseling program utilizing the WDEP technique was designed as an alternative guidance and counseling service to improve students' grit.